Angelitotoo? adolescent fatherhood in television and real life - Addun, Ana Patricia G. 1991-; Bolongan, Hope R. (2013)
"This undergraduate thesis explores the reality of adolescent fatherhood as portrayed in the television drama series Angelito: Batang Ama. This analysis of realism in a television show is important in understanding how accurately media presents an important social issue. Previous literature has shown more accounts of young mothers' experiences in line with the increased incidences of teenage pregnancy in some countries, including the Philippines. However, little is known about the experiences of the young fathers. Therefore, the current study aims to identify expectations, responsibilities, fears, and challenges of actual fathers as well as those of the series' lead characters, Angelito. In order to understand how the lead character was conceptualized and shapes, a focus interview with one of the show's writers and textual analysis of the program's first season were employed. Actual young fathers were then interviewed to verify if the series is a valid representation of these young fathers' experiences. Findings show that the televised father Angelito positively resembles actual adolescent fathers' experiences-particularly their expectations, responsibilities, fears and challenges. The television drama series Angelito: Batang Ama is found to be realistic based on the huge resemblance between Angelito's experiences and those of actual adolescent fathers, which is supported by Williams' (1977) characteristics of social realism on television."